2012
DOI: 10.1371/journal.pbio.1001266
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms Underlying Motivation of Mental Versus Physical Effort

Abstract: Mental and physical efforts, such as paying attention and lifting weights, have been shown to involve different brain systems. These cognitive and motor systems, respectively, include cortical networks (prefronto-parietal and precentral regions) as well as subregions of the dorsal basal ganglia (caudate and putamen). Both systems appeared sensitive to incentive motivation: their activity increases when we work for higher rewards. Another brain system, including the ventral prefrontal cortex and the ventral bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
246
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(278 citation statements)
references
References 64 publications
16
246
1
5
Order By: Relevance
“…Dopamine function, which has long been implicated in willingness to expend effort (Salamone, 2009;Salamone et al, 2007;Treadway et al, 2012b), may also act on these regions to affect effortful decision making (Schweimer and Hauber, 2006;Schweimer et al, 2005), and thus its contribution to cognitive effort is currently under study. The overlapping-yet-distinct effects observed in the present experiments suggest that regions not required for physical effort-based decision making, such as the prefrontal cortex, may in fact be necessary for decision making with cognitive effort costs (Schmidt et al, 2012), and the NAc' prevalence in the effort literature warrants future consideration of its involvement in choice on the rCET. To conclude, these results may disentangle the unique contributions of the BLA and ACC, namely the subjective valuation of options vs the biasing of behavior toward advantageous choice strategies, respectively, and offer unique insights into targeting these regions for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Dopamine function, which has long been implicated in willingness to expend effort (Salamone, 2009;Salamone et al, 2007;Treadway et al, 2012b), may also act on these regions to affect effortful decision making (Schweimer and Hauber, 2006;Schweimer et al, 2005), and thus its contribution to cognitive effort is currently under study. The overlapping-yet-distinct effects observed in the present experiments suggest that regions not required for physical effort-based decision making, such as the prefrontal cortex, may in fact be necessary for decision making with cognitive effort costs (Schmidt et al, 2012), and the NAc' prevalence in the effort literature warrants future consideration of its involvement in choice on the rCET. To conclude, these results may disentangle the unique contributions of the BLA and ACC, namely the subjective valuation of options vs the biasing of behavior toward advantageous choice strategies, respectively, and offer unique insights into targeting these regions for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 57%
“…Broadly speaking, cognitive or mental effort costs are those that are non-physical in nature and tax limited neurobiological resources, as observed through the psychological constructs of working memory, attention, response inhibition, etc. (Schmidt et al, 2012). Regions deemed inessential in physical effort (eg, the prefrontal cortex; Walton et al, 2003b) have been shown to have a prominent role in human cognitive effort Schmidt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to effort, conflict monitoring has recently been proposed to register as a cost 1 , particularly mediated by midcingulate cortex (MCC). Yet, existing empirical support for MCC involvement in conflict costs have largely relied upon explicit manipulations of cognitive effort, and not conflict per se [2][3][4][5] . While some studies have demonstrated aversion-inducing effects of response conflict, these studies did not examine the neural mechanisms by which this effect is instantiated 2,6,7 .…”
mentioning
confidence: 99%
“…The paradigm was adapted from previous experiments that demonstrated the implication of the ventral striato-pallidal complex in incentive motivation, i.e., in energizing behavioral performance as a function of the reward at stake (8,9). The task (Fig.…”
mentioning
confidence: 99%